2017
DOI: 10.1002/smll.201702288
|View full text |Cite
|
Sign up to set email alerts
|

Bioadhesive Polymersome for Localized and Sustained Drug Delivery at Pathological Sites with Harsh Enzymatic and Fluidic Environment via Supramolecular Host–Guest Complexation

Abstract: Targeted and sustained delivery of drugs to diseased tissues/organs, where body fluid exchange and catabolic activity are substantial, is challenging due to the fast cleansing and degradation of the drugs by these harsh environmental factors. Herein, a multifunctional and bioadhesive polycaprolactone-β-cyclodextrin (PCL-CD) polymersome is developed for localized and sustained co-delivery of hydrophilic and hydrophobic drug molecules. This PCL-CD polymersome affords multivalent crosslinking action via surface C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…[27][28][29][30] Compared to various nanochemical polymers (upconversion nanotransducer-based nanocomplexes, nanocomposite hydrogels, or supramolecular hydrogels), TFNA not only possesses good biocompatibility and biodegradability and the ability to permeate cells but can also be functionalized via modification with DNA fragments, RNAs, polypeptide monomers, and small-molecule drugs. [31][32][33][44][45][46] In our previous studies, we found that TFNA can enhance the proliferation and migration of chondrocytes and maintain their morphology at an optimum concentration of 250 nmol·L −1 . 21,22 Upon consideration of these characteristics, TFNA was used in combination with wogonin, a naturally occurring flavonoid with various biological properties, such as anti-inflammatory and anti-cancer activity.…”
Section: Discussionmentioning
confidence: 92%
“…[27][28][29][30] Compared to various nanochemical polymers (upconversion nanotransducer-based nanocomplexes, nanocomposite hydrogels, or supramolecular hydrogels), TFNA not only possesses good biocompatibility and biodegradability and the ability to permeate cells but can also be functionalized via modification with DNA fragments, RNAs, polypeptide monomers, and small-molecule drugs. [31][32][33][44][45][46] In our previous studies, we found that TFNA can enhance the proliferation and migration of chondrocytes and maintain their morphology at an optimum concentration of 250 nmol·L −1 . 21,22 Upon consideration of these characteristics, TFNA was used in combination with wogonin, a naturally occurring flavonoid with various biological properties, such as anti-inflammatory and anti-cancer activity.…”
Section: Discussionmentioning
confidence: 92%
“…Polymersomes are self‐assembling artificial vesicles comprised of an enclosed bilayer membrane formed using amphiphilic block copolymers . The polymers forming the bilayer shell structure typically have three block copolymer variations, including a diblock copolymer AB and two triblock variants, ABA and ABC, where A and C represent distinct hydrophilic polymers and B represents a hydrophobic polymer …”
Section: Methods and Effects Of Incorporating Inorganic Nps Into Drugmentioning
confidence: 99%
“…Noncovalent interactions between complementary groups -Mixing-induced two-component hydrogels [53] -DNA-PNA methacrylamide hydrogels [72] -DNA-polypeptide hydrogels [73] -Enantiomer-functionalized dextran hydrogels [74] -Host-guest cyclodextrin hydrogels [76] -Cucurbit[n]uril hydrogels [77] Covalent crosslinking -Gelatin-based hydrogels [11,55,63] -Collagen-based hydrogels [54] -Fibrinogen-based hydrogels [56] -Chitosan-based hydrogels [57] -Alginate-based hydrogels [64] -HA-based hydrogels [65,66] -PEG-based hydrogels [58,[60][61][62]66,67,[69][70][71] Nanoparticle-based -Methylcellulose-based hydrogels [78,79] -HA-based hydrogels [79,82] -PEG-based hydrogels [80,81,84] -DNA-based hydrogels [83] Change in pH…”
Section: Component Mixingmentioning
confidence: 99%
“…Host-guest hydrogel networks have also been formed through the complexation of adamantane-functionalized polymersomes and HA modified with β-cyclodextrins. [82] A similar approach can be taken using DNA hybridization, for example, hydrogel networks have been assembled from six-arm DNA strands annealed with complementary DNA sequences bound to various gold nanostructures. [83] More recently, hydrogels have been assembled using coordinate covalent bonds formed between carboxylated magnetic iron oxide nanoparticles and catechol-functionalized polymer chains.…”
Section: Electromagnetic Radiationmentioning
confidence: 99%